Abdominal Sacral Colpopexy In Treatment Of Vaginal Vault Prolapse: By Less Invasive Method (Bangladesh Journal of Obstetrics & Gynaecology, 2013)
Objective: To assess the outcomes of abdominal sacral colpopexy in less invasive method. Study design: It was a prospective study conducted in Comilla Medical College Hospital and Comilla General Hospital during the period from 2005 to 2009.Method: Thirty women with vaginal vault prolapse were selected by inclusion and exclusion criteria in a consecutive, exhaustive method. Primary outcome measurements were included subjective, objective and patient-determined success rate. Secondary outcome included the impact on bowel, bladder, sexual function and quality of life. Result: Result shows that, vault prolapse is mostly associated with older patients, age more than sixty (66.7%), para >5 (60%) and menopausal women (66.7%). Vault prolapse was mostly associated with cystocele (93.3%), stress incontinence (76.7%) and more common following abdominal hysterectomy (70%). During operation the dissection was less (3-4cm). Average operating time was 54.33/min; average estimated blood loss was 49.17/ml. One patient required blood transfusion, one developed haematoma during surgery, no gut injury or haemodynamic instability developed. Post operatively, no internal haemorrhage, 4 patient developed fever (13.3%), wound infection one (3.3%), UTI 4 patients (13.3%), no voiding difficulty or thromboembolism and one patient developed mesh rejection (3.3%). After one year follow-up success rate was 96.7%. Conclusion: Abdominal sacral colpopexy is a safe and effective method for correction of vaginal vault prolapse. DOI: http://dx.doi.org/10.3329/bjog.v25i1.13723 Bangladesh J Obstet Gynaecol, 2010; Vol. 25(1) : 3-8